Experimental study of a heart pump - Chong, Choon Fei. (2009)
This project involves the re-design and fabrication from an existing heart pump prototype. The concept involves a revolutionary idea of a rotating positive displacement pump. Several initial conceptual designs were first being explored and reviewed. The final design, with the elimination of an intermediary shaft that connects the motor to the roller of the pump and a flat surface in the bottom housing of the pump that enables full compression of a Polyurethane U-Tube without any backflow as experienced by the previous pump prototype is being designed. Slight modifications were also done to the mould design and the Polyurethane (80A) U-Tube fabrication to go in accord with the new pump design and the modifications have been detailed in the report. Test apparatus and the experimental set-up were next prepared and the new pump was fabricated to test out its efficiency. Experiments were then carried out and two conclusions can be drawn. Firstly, at each of the fixed motor speeds, the flowrates are now consistent at various pressure differences (between free pressure to 180 mmHg), which fulfills the characteristic of a positive displacement pump. Secondly, with the pressure maintained at 120 mmHg, positive test results confirmed the functionality of the new pump prototype for a flow rate of 1.243 to 2.470 litres per minute, between motor speeds range of 1000 rpm to 2200 rpm. This showed a 92% increase in flowrate for the Polyurethane (80A) U-Tube using the new pump design at the 2000 rpm mark, as compared to the previous pump prototype.